MEMPELAJARI REAKSI ISOMERISASI SAFROL DENGAN PEREAKSI t-BuOK/DMSO DAN KOH/CH2OHCH2OH - Gugule, Sanusi; Fatimah, Feti (CHEMISTRY PROGRESS, 2009)
The studies have been done about the transformation of safrole into isosafrole. The transformation wasdone using reagents, namely t-BuOK/DMSO and KOH/CH2OHCH2OH. The purities of all products weretested with thin layer and gas chromatography. Thereafter the structures were identified with infraredspectrophotometers, NMR1H and 13C spectrometry, and mass spectrometry. The isomerization product ofsafrole into isosafrole with highest percentage yield (97%) was given t-BuOK/DMSO.